Combination of Stem Cell & PRP Therapy in Healthy Aging for Osteoarthritis - Susanti Vinski, Deby; Cinta Vinski, Natasha; Sintong, Langga; Hardjo, Marhaen (Riviera Publishing, 2024)
Osteoarthritis is the most common inflammation of the joints, with symptoms of joint pain when moving, stiffness, especially in the morning, weakening of the muscles around the problematic joint, sound when the joint is moved, and swelling in the joint area. The absence of treatment that can eliminate Osteoarthritis has led to an increasing demand for more effective treatment. In fact, common disease is age-related, and global statistics show that it is a significant health problem and financial burden on health and social welfare systems globally. This study aims to explain and analyze the effectiveness of combination therapy of stem cells and PRP in the treatment of Osteoarthritis. The research method used is a case study where combination therapy of stem cells and PRP offers the potential to modify the natural recovery of knee Osteoarthritis using stem cell-based technology. Stem cell therapy was given to 9 Osteoarthritis patients aged over 50 years, most of whom were female, who were proven to tend to improve their condition after undergoing stem cell therapy with PRP at the Vinski Regenerative Center and were able to carry out their daily activities again.